Characteristics of Point-Bar Development under the Influence of a Dam: Case Study on the Dráva River at Sigetec, Croatia - Kiss, Tímea; Balogh, Márton (Journal of Environmental Geography, 2015)
Before the extensive engineering works the Dráva River had braided pattern. However in the 19-20th centuries river regulation works became widespread, thus meanders were cut off, side-channels were blocked and hydroelectric power plants were completed. These human impacts significantly changed the hydro-morphology of the river. The aim of the present research is to analyse meander development and the formation of a point-bar from the point of view of indirect human impact. Series of maps and ortho-photos representing the period of 1870-2011 were used to quantify the longterm meander development, rate of bank erosion and point-bar aggradation. Besides, at-a-site erosion measurements and grain-size analysis were also carried out. As the result of reservoir constructions during the last 145 years floods almost totally disappeared, as their return period increased to 5-15 years and their duration decreased to 1-2 days. The channel pattern had changed from braided to sinuous and to meandering, thus the rate of bank erosion increased from 3.7 m/y to 32 m/y. On the upstream part of the point-bar the maximum grain size is 49.7-83.4 mm and the mean particle size is 7.6 mm, whilst on the downstream part the maximum grain size was only 39.7-39.9 mm and mean sediment size decreased to 6.1 mm. Due to the coarse sediment supply and the decreasing stream energy the point-bars develop quickly upstream and laterally too.